Proposal for delimiting a Conservation Unit in the Alto Sertão Paraibano: the case of the Engenheiro Ávidos Ecological Park (Research, Society and Development, 2022)
Brazil has an extensive framework of Conservation Units (UC), at present, according to the National Registry of Conservation Units, there are 2,201 UC, whether in federal, state, district and municipal areas, which together cover almost 30% of the national territory. The Engenheiro Ávidos Ecological Park (PECEA), Cajazeiras - PB, was created with the objective of preserving the native vegetation and fauna of the region, in addition to promoting ecotourism and environmental education, however, the decree of its creation does not mention the geographical limits, the land situation, nor the activities to be developed in the surrounding areas. Thus, this study has as its main objective to construct a delimitation proposal for the PECEA, by identifying the legal and environmental criteria for its delimitation. The research is based on field visits, on-site surveys and analysis of satellite images for the construction of maps. Regarding legislation, the Law No. 9985 of July 18, 2000 (SNUC) and the Organic Law of the Municipality were studied. The research resulted in the construction of the Park's delimitation along with the study of slope and its geopositioning. It is hoped that this study can be an instrument that promotes conservation on both a local and regional scale, ensuring the integration of the UC with the territory and arousing the interest of academics to the theme and/or the use of geotechnologies in the preparation of their work, as well as the adoption of conservationist practices.